Pelatihan Pembuatan Platform Digital Marketing pada Usaha Kecil dan Menengah di Desa Lembang Baji - Akram Akram; Nasir Nasir; Nurindah Nurindah; Rauddin Rauddin; Sulis Rifka Afifah; Aldi Saputra (I-Com: Indonesian Community Journal, 2024)
Business opportunities in agriculture are very promising because they concern the needs of daily life, the benefits are also very attractive if managed properly. Population growth makes businesses in the agricultural sector a growing business. The business of cultivating land and planting various types of crops needed such as vegetables, fruits, rice, corn and spices is the main business in agriculture. Another business in agriculture is sugar areng which is the spearhead of the most profitable livelihood in Dusung Kota Intang, Lembang Baji Village. The Harapan Jaya Farmers Group is a farmer group that has existed for a long time so that it has changed its membership. The Harapan Jaya farmer group has 29 members, all of whom have a farmer background. At this PM event, women and men were brought in from their words from the Harapan Jaya farmer group, Dusung Kota Intang who has entrepreneurship training and may be part of the Small Scale, Little and Medium Ventures (MSMEs) segment which is influenced by the impact of advanced promotions so that there is a problem that the character of MSMEs on the screen tends to be moo in utilizing innovation, marketing problems with reduced transaction turnover, and problems in product distribution.